Changes in spinal inhibitory networks induced by furosemide in humans. (3rd June 2014) - Klomjai, Wanalee; Lackmy‐Vallée, Alexandra; Katz, Rose; Bussel, Bernard; Bensmail, Djamel; Lamy, Jean‐Charles; Roche, Nicolas
Abstract : Key points: It has been demonstrated in humans that furosemide crosses the blood–brain barrier and blocks activity in the epileptic brain. In this study, we demonstrated using non‐invasive electrophysiological techniques in healthy human subjects that furosemide, a cation‐chloride co‐transporter blocker, orally administered at doses commonly used in the clinic (40 mg), reduces the efficacy of pre‐ and postsynaptic inhibition of soleus motoneurons in the spinal cord. Furosemide can be a useful tool to detect the intrinsic functioning of inhibitory synapses and to explore if the reduced inhibitory interneuronal activity that probably contributes to spasticity also exists in humans with spinal cord injury. Abstract: During neural development in animals, GABAergic and glycinergic neurons are first excitatory, and then become inhibitory in the mature state. This developmental shift is due mainly to strong expression of the cation‐chloride K–Cl cotransporter 2 (KCC2) and down‐regulation of Na–K–Cl cotransporter 1 (NKCC1) during maturation. The down‐regulation of co‐transporter KCC2 after spinal cord transection in animals leads to the depolarising (excitatory) action of GABA and glycine and thus results in a reduction of inhibitory synaptic efficiency. Furosemide, a loop diuretic, has been shown to selectively and reversibly block inhibitory postsynaptic potentials without affecting excitatory postsynaptic potentials in animal spinal neurons. Moreover, this diuretic has been also demonstrated to block the cation‐chloride co‐transporters. Here, we used furosemide to demonstrate changes in spinal inhibitory networks in healthy human subjects. Non‐invasive electrophysiological techniques were used to assess presynaptic inhibition, postsynaptic inhibition and the efficacy of synaptic transmission between muscle afferent terminals and soleus motoneurons in the spinal cord. Orally administered furosemide, at doses commonly used in the clinic (40 mg), significantly reduced spinal inhibitory interneuronal activity for at least 70 min from intake compared to control experiments in the same subjects while no changes were observed in the efficacy of synaptic transmission between muscle afferent terminals and soleus motoneurons. The reduction of inhibition was dose‐dependent. Our results provide indirect evidence that reversible changes in the cation‐chloride transport system induce modulations of inhibitory neuronal activity at spinal cord level in humans.